Sorting through Cheap Talk: Theory and Evidence from a Labor Market - John J. Horton; Ramesh Johari; Philipp Kircher (Institute of Labor Economics (IZA), 2024)
In a labor market model with cheap talk, employers can send messages about their willingness to pay for higher-ability workers, which job-seekers can use to direct their search and tailor their wage bid. Introducing such messages leads – under certain conditions – to an informative separating equilibrium that affects the number of applications, types of applications, and wage bids across rms. This model is used to interpret an experiment conducted in a large online labor market: employers were given the opportunity to state their relative willingness to pay for more experienced workers, and workers can easily condition their search on this information. Preferences were collected for all employers but only treated employers had their signal revealed to job-seekers. In response to revelation of the cheap talk signal, job-seekers targeted their applications to employers of the right "type," and they tailored their wage bids, affecting who was matched to whom and at what wage. The treatment increased measures of match quality through better sorting, illustrating the power of cheap talk for talent matching.
Keywords: J64; D83; C87; 330; sorting; cheap-talk; gig-economy; freelancer; field-experiment; online job search platform